Untangling the Causes of Land Ownership Disputes - Maryam Naway; Nurul Fazri Elfikri (Estudiante Law Journal, 2022)
The purpose of this study is to find out and analyze the role of the village head as a mediator in resolving land title disputes in Tongo Village, Bonepantai District, and Bonebolango Regency. This research uses a type of empirical legal research, with a qualitative research approach that uses facts in the field as the main data source. The data sources used are the results ofobservation, interviews in the field, and documentation. The population and samples used are village heads and communities in dispute in Tongo Village. The results showed that (1) the settlement of land disputes in Tongo Village through the mediation of the Village Head is quite effective because it always strives to obtain mutual benefits and does not require a lot of costs, is more efficient, and still maintains good relations between the community; (2) while the factors causing land disputes in Tongo Village are the use of land without permission from the landowner, unclear division of inheritance, uncertified land, and land boundary disputes.